PENERAPAN KONSEP COST REDUCTION PROGRAM DALAM UPAYA MENURUNKAN BIAYA DISTRIBUSI RUMAH PAKAN LELE ABAH HERMAN - Dhea Ayu Lestari; Muchamad Iqbal Taufik T; Heru Rachman (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
Abah Herman Catfish Feed House is one of the animal feed distributors in the Bandung City area that distributes catfish feed to the ciganitri and cijambe areas Over the past few years there has been an increase in shipping costs due to an increase in maintenance costs and other costs which has resulted in a decrease in shop profits. Therefore, a way is needed that can reduce the cost of such distribution. One way that can be done is to identify and analyze the factors causing the increase in distribution costs by applying the kaizen concept with the PDCA (Plan – Do – Check – Action) stage, which first selects the type of transportation mode that previously used cars to switch to using motorcycles. The process of data processing in solving problems with the PDCA method will be easier to do with the support of the points in the kaizen and cost reduction programs. The result of the evaluation of the implementation of the cost reduction program concept with Kaizen costing PDCA is a decrease in distribution costs by 6.5% after the replacement of transportation modes using 2 vario 150 motorcycles